Producing actionable science in conservation: Best practices for organizations and individuals. Issue 12 (24th October 2020) - Gerber, Leah R.; Barton, Chris J.; Cheng, Samantha H.; Anderson, Derrick
Abstract : Abstract: Many researchers working in conservation aspire to produce "actionable science" to inform conservation practice. In order to understand what it takes to produce actionable science, we interviewed 71 researchers who have worked on producing actionable science in conservation. We asked about the attributes of actionable science and the various factors that, in their experience, aid or hinder its production. We focused specifically on factors that correspond to individual behaviors and those that relate to organizational level policies and practices. Six best practices associated with the production of actionable science emerged from our interviews: four at the individual level and two at the organizational level. Best practices for individual behaviors include: (a) engaging in collaboration; (b) practicing empathy; (c) building trusting relationships; and (d) employing diverse communication methods. Best practices for organizations include: (a) incentivizing actionable science and (b) providing resources for actionable science to early‐career researchers. Our analyses provide useful guidelines for conservation researchers and practitioners who are interested in producing actionable science.